Clinical behaviour of patients exposed to organic dust and diagnosed with idiopathic pulmonary fibrosis. Issue 12 (13th June 2018) - De Sadeleer, Laurens J.; Verleden, Stijn E.; De Dycker, Els; Yserbyt, Jonas; Verschakelen, Johny A.; Verbeken, Eric K.; Nemery, Benoit; Verleden, Geert M.; Hermans, Frederik; Vanaudenaerde, Bart M.; Wuyts, Wim A.
Abstract: Background and objective: Although idiopathic pulmonary fibrosis (IPF) patients experience a worse survival compared with chronic hypersensitivity pneumonitis (CHP), organic dust exposure is a known risk factor for both IPF and CHP. Methods: We divided patients diagnosed with IPF, based on their exposure to moulds/birds (absent: group A; present: group B). We retrospectively compared pulmonary function and survival between groups A and B, and a separate CHP cohort (group C). Results: A total of 293 patients were included (group A: n  = 171, group B: n  = 73, group C: n  = 49). Demographics and baseline pulmonary function did not differ between groups A and B, but significant differences were seen between groups B and C. Median survival of group B was 84 months, which was longer than group A (43 months, P  = 0.002), but lower than group C (157 months, P  = 0.04), in both univariate and multivariate analyses. Antifibrotic treatment resulted in a better outcome in group A (hazard ratio (HR): 0.44) and group B (HR: 0.12) without interaction between exposure and antifibrotic use ( P  = 0.20). Forced vital capacity (FVC) decline was not associated with mould/bird exposure in this cohort. Conclusion: Group B patients experienced a better outcome compared with (non‐exposed) IPF patients, although worse compared with CHP patients. Antifibrotic treatment in group B resulted in a similar beneficial effect compared with group A. Further research is needed to ascertain the diagnostic designation in this exposed usual interstitial pneumonia (UIP) patient group without other CHP features. Abstract : Usual interstitial pneumonia (UIP) patients exposed to moulds or birds without other features of chronic hypersensitivity pneumonitis (CHP) experience a better survival compared with non‐exposed idiopathic pulmonary fibrosis (IPF) patients, although still worse compared with definite CHP patients. A similar beneficial effect from antifibrotics was seen irrespective of mould/bird exposure.